Improvements in clinical response between 12 and 24 weeks in patients with rheumatoid arthritis on etanercept therapy with or without methotrexate. Issue 10 (5th June 2008) - Kavanaugh, A; Klareskog, L; van der Heijde, D; Li, J; Freundlich, B; Hooper, M
Abstract : Background: Whereas many patients respond quickly to treatment with tumour necrosis factor (TNF) inhibitors, some patients may experience significant but delayed responses. Objective: To evaluate the clinical response between 12 and 24 weeks in subjects with rheumatoid arthritis from the Trial of Etanercept and Methotrexate with Radiographic Patient Outcomes. Methods: Clinical response was assessed at 24 weeks in 12-week non-responders, according to American College of Rheumatology (ACR) response criteria. The proportion of subjects who successfully maintained response to 52 weeks was analysed, as were radiographic outcomes. Results: Data from 682 subjects were included in the analysis. Non and partial responders in all three groups (etanercept, methotrexate and etanercept plus methotrexate) at week 12 showed an improvement in responses at week 24. Over 80% of the week 24 ACR20/50/70 responders in the etanercept plus methotrexate arm sustained their response to 52 weeks. In the etanercept arms, a delayed clinical response was not associated with increased radiographic progression at week 52. Conclusion: A significant proportion of non and partial responders to etanercept with or without methotrexate therapy at week 12 achieved a good clinical response or improved their overall clinical response at week 24. Discontinuing TNF inhibitor therapy at 12 weeks may be premature in some rheumatoid arthritis patients.